PELATIHAN PENULISAN KARYA ILMIAH UNTUK MENINGKATKAN KETERAMPILAN MENULIS BAGI GURU SEKOLAH DASAR DI KOTA SEMARANG - Djariyo IKIP PGRI Semarang; Joko Suliyanto; Mudzanatun IKIP PGRI Semarang; Fine Reffiane; Iin Purnamasari (E-Dimas: Jurnal Pengabdian kepada Masyarakat, 2011)
Abstract ?é?á It is fact, there are still a few of elementary teachers write an article in newspapers or present their article in regional / nasional seminar. Consequently, they will face obstacles in increasing their grade. Based on the survey, we found that many elementary teachers in Semarang still have no idea in how to make a good article. Also, there is no Journal for elementary teachers as a media for them in delivering their articles in order to have some credits. Based on that case, team of community service try to give them some trainings; how to design a classroom research, and how to make a good article. By having these, they are expected to be able to find their topic and design their classroom research, then they will make its article that can be sent to the newspapers or journal. Automatically, they will have some credits to raise their grade and they will be prosperous. The trainings were given to 37 elementary teachers of KKG Jendral Sudirman / teachers?óÔé¼Ôäó group of Jendral Sudirman. We found that actually there is one teacher who has experience in conducting a classroom research, but still there are many teachers who are less in making a research and article. After understanding the material, then they try making a classroom research and designing it into an article. ?é?á Key words; writing an article, a classroom research, credits ?é?á